The knowledge absorptive capacity to improve the cooperation and innovation in the firm - Lourdes Saiz; David Pérez-Miguel; Miguel Ángel Manzanedo-del-Campo (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The purpose of this paper is to study the absorptive capacity types in the knowledge management literature and aims to understand how companies can strength their contexts of cooperation in order to innovate. Design/methodology/approach: A balanced panel of 1,220 firms that respond to the Survey of Business Strategies for a three-year period was used, which represents a total of 3,660 observations. Findings: The justification of absorptive capacity typology for an innovation efficiency process. The influence of the potential and realized absorptive capacity on new products is significant and causes effects on internal research and development in diverse way. The impact of the joint ventures, suppliers' cooperation and customers' cooperation are significant on absorptive capacity. Research limitations/implications: It would be interesting to extend the research to another innovation metrics as new organizational methods, new processes, new designs or new methods in the use of sales channels. Practical implications: The agreement of cooperation activities constitutes an important decision for the firm's innovation. Companies must be conscious that while suppliers and customers' cooperation are relevant cooperation actions to increase the internal research and development, joint ventures and customers' cooperation are significant to the growth of the new products. Social implications: The types of absorptive capacity and internal research and development serve as mediating mechanisms between cooperative activities and innovative performance. Originality/value: This paper advances the literature on absorptive capacity by showing how firms use their positions of technological vigilance and management to form their capabilities, and subsequently, to enhance innovation outcomes. This study considers it is necessary to analyze the typology of the absorptive capacity that can allow managers to understand an innovation efficiency process in the cooperation context and make better decisions. The confluence of cooperation activities, absorptive capacity and organizational objectives in internal research and development obtain higher innovative results.
Keywords: 650; knowledge management; absorptive capacity; intellectual capital; innovation; cooperation; panel model